Tumor control and survival after postoperative radiotherapy for high-risk oral cavity cancer: A retrospective cohort study - Pepijn B Bolleurs; Brend P Jonker; Joris BW Elbers; Gerda M Verduijn; Atilla Gül; Aniel Sewnaik; Wilma D Heemsbergen (Clinical and Translational Radiation Oncology)
Background: We evaluated locoregional failure (LRF) and survival after postoperative radiotherapy (PORT) in selected high-risk oral squamous cell carcinoma (OSCC) patients. Methods: In a retrospective OSCC cohort (n = 219) treated with local (n = 216) and/or regional (n = 87) PORT in 2011–2018, we determined the first location of tumor recurrence or progression, survival, and cause of death. Tumor control and survival was calculated using Kaplan Meier method. Prognostic factors were evaluated in Cox regression models. Results: Main subsites were oral tongue (34 %), gingiva (32 %), and floor of mouth (27 %). Eight percent also received chemotherapy. Median follow-up was five year for tumor control and eight year for survival. Tumor progression was observed in 47 patients (n = 31 LRF). Nine patients had salvage treatment. Locoregional control was 87 % and 84 % at 2 and 5 years, respectively. Significant prognostic factors for local failure (LF) were T4 stage, bone invasion, and subsite gingiva; 12 of 18 LF concerned a T4 gingiva tumor with bone invasion. For regional failure (RF), pN1 (vs pN0) was prognostic, mainly concerning solitary contralateral RFs. Overall survival was 63 % and 48 % at 5 and 8 year, respectively. Main causes of death (104 events) were the index tumor (n = 42) and a post-treatment second primary tumor (n = 37). Conclusion: A locoregional control of 84 % was achieved after PORT for high-risk OSCC with only 8 % receiving additional chemotherapy. Overall survival was 48 % at 8 years, with a large proportion of cancer-related deaths related to the index tumor and other subsequent tumor diagnoses. Risk of LF was increased for gingiva tumors with bone invasion. N1 stage was associated with a risk of solitary contralateral RFs in non-irradiated neck areas.